Dimensions of authenticity in Malay cuisine from experts' perspectives - Hamzah, Humairah; Abdul Karim, Muhammad Shahrim; Othman, Mohiddin; Hamzah, Azimi (Mediterranean Center of Social and Educational Research, 2013)
Food authenticity is defined as the originality and genuine of Malay cuisine in various aspects. It is an important element in portraying the family identity, culture and heritage of Malay community in Malaysia. Food experts including professional chefs and cooks are believed the parties that still practising and maintaining the authenticity of Malay cuisine in today’s scenario. Hence, in-depth interviews were individually conducted among the Malay food experts (n=15) in each State in Peninsular Malaysia to seek how an experts interprets the meaning and characteristics of authenticity in Malay cuisine that influenced the taste of the food. Technically, the food experts were chosen based on the diverse understanding, skills and experiences in Malay cuisine. Furthermore, the interview data were strengthened with extensive observation in their food outlets. Consequently, data analysis by using a self determination theory approach revealed that Malay food experts’ personality and motivation were directly accessed them to view the authenticity of Malay cuisine in three dimensions. There were consists of family culture (relational orientation, value, cooking skill, cooking method, cooking utensil and cooking ingredients), self interest (hobby, passion, permanent job, financial and events), and awareness (authentic taste, texture and appearance, modification, and alteration) characteristics. In a nutshell, these empirical findings demonstrated how a model of dimensions of authenticity in Malay cuisine and the characteristics able to influence the authentic taste of the cuisine from the experts’ perspective and served as guidance for future researches and interventions in Malay cuisine authenticity.